The memoir and the memoirist : reading and writing personal narrative - Larson, Thomas, 1949- (Swallow Press/Ohio University Press, 2007)
The memoir is the most popular and expressive literary form of our time. Writers embrace the memoir and readers devour it, propelling many memoirs by relative unknowns to the top of the best-seller list. Writing programs challenge authors to disclose themselves in personal narrative. Memoir and personal narrative urge writers to face the intimacies of the self and ask what is true. In The Memoir and the Memoirist, critic and memoirist Thomas Larson explores the craft and purpose of writing this new form. Larson guides the reader from autobiography and the personal essay to the memoir--a genre focused on a particularly emotional relationship in the author's past, an intimate story concerned more with who is remembering, and why, than with what is remembered. The Memoir and the Memoirist touches on the nuances of memory, of finding and telling the truth, and of disclosing one's deepest self. It explores the craft and purpose of personal narrative by looking in detail at more than a dozen examples by writers such as Mary Karr, Frank McCourt, Dave Eggers, Elizabeth Wurtzel, Mark Doty, Nuala O'Faolain, Rick Bragg, and Joseph Lelyveld to show what they reveal about themselves. Larson also opens up his own writing and that of his students to demonstrate the hidden mechanics of the writing process. For both the interested reader of memoir and the writer wrestling with the craft, The Memoir and the Memoirist provides guidance and insight into the many facets of this provocative and popular art form.